Oil Production, Refining and Transportation in Canada - I. A. Guliyev; I. I. Litvinyuk (Vestnik MGIMO-Universiteta)
The article deals with fuel and energy complex of Canada as one of the largest manufacturers of primary energy in the world, which provides up to 6 percent of the world energy supply. Only the Russian Federation, PRC, the United States of America and the Kingdom of Saudi Arabia have larger production volumes. However, oil plays the most significant role in Canada's energy exports. It is estimated that its proven reserves are sufficient to meet the demand for 140 years at current production rate. The relevance of the study, including the analysis of fuel and energy complex of Canada, is due to the fact that such comparison and synthesis of data on the amount of recoverable oil reserves, the volume of its production, imports, exports and transit of oil and oil products, the distribution of oil for transportation (via pipelines, rail, sea, road), strategic oil field, refining and transportation of oil and oil products development projects, as well as implementation of Canada's best practices in the Russian Federation, is being developed for the first time. In addition, the data given in previously published articles on the subject, due to the dynamic development of the industry, are obsolete and do not reflect the real situation.